Age-related changes in functional hemispheric asymmetry : an fMRI study. - Heng, Gladys Jiamin (2013)
Global aging has increased the pace and significance to study age-related neural changes to better understand the aging process and prevent related diseases. Neuroimaging literature in aging has suggested cereberal symmetry, a well-established phenomenon, to be less prominent in the elderly in the prefrontal cortex (Cabeza, 2002). This is known as the hemispheric asymmetry reduction in older adults (HAROLD). Although there is extensive literature on language and visuospatial processing, there seems to be a lack of research investigating the age-related changes that accompany these processes. This study aims to investigate age-related changes in functional hemispheric asymmetry by examining language processing, which is known to be left-lateralized, and visuospatial processing, which is known to be right-lateralized. Tasks utilizing homophone judgment and line orientation judgment were designed to elicit these processes respectively. Grey matter atrophy was accounted for by using the grey matter probability maps created from Diffeomorphic Anatomical Registration Through Exponentiated Lie Algebra (DARTEL) as covariates in analyses and AveLI was used to provide a quantitative measurement of functional lateralization. Results showed that the homophone judgment task produced left-lateralization in frontal regions for both young and older adults. Right fronto-parietal activations were seen when line orientation was contrasted against homophone judgment in both groups. Although AveLI scores were not significantly different, older adults showed increased bilateral frontal activity for both tasks. Our data thus provide more support for the compensation-related utilization of neural circuits hypothesis (CRUNCH) rather than the HAROLD model.